2020
DOI: 10.1177/0194599820930244
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Management of COVID‐19: A Multi‐institutional Otolaryngology Perspective

Abstract: Objective To provide evolving information on active protocols regarding inpatient, outpatient, procedural, and surgical case management taking place in otolaryngology practices in response to COVID-19. Study Type Cross-sectional multi-institutional survey. Methods An online survey of 55 otolaryngology departments across North America. Results As of March 25, 2020, almost all (n = 53 of 55, 96.3%) otolaryngology departments had canceled elective cases and were performing only urgent consults. Most residents con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
0
11
1
Order By: Relevance
“…Otorhinolaryngology clinics around the world are reorganizing outpatient services to sustain patient care and to minimize the transmission of the disease [34,35]. Because many Otorhinolaryngologic examinations are aerosol producing examinations, it is important to determine which patients are at higher risk of disease transmission and take necessary precautions accordingly [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Otorhinolaryngology clinics around the world are reorganizing outpatient services to sustain patient care and to minimize the transmission of the disease [34,35]. Because many Otorhinolaryngologic examinations are aerosol producing examinations, it is important to determine which patients are at higher risk of disease transmission and take necessary precautions accordingly [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In assessing the possible factors contributing to these trends, it may be important to recognize the 34.4% reduction in RSV for "ENT" as the context for the decreases seen in the other terms. This decrease in "ENT" queries could reflect the reduction in referrals to otolaryngologists and the widespread cancellations of elective surgeries [20]. Previous studies have shown that patients utilize more internet search terms after receiving a diagnosis as compared to before it has been given [21].…”
Section: Discussionmentioning
confidence: 99%
“…These aforementioned risks and concerns over lack of personal protective equipment (PPE) in the United States at the time led the American Academy of Otolaryngology-Head and Neck Surgery to release a position statement early in the pandemic (March 23, 2020) recommending that otolaryngologists limit patient care to time-sensitive and emergent problems and routinely use appropriate PPE when treating patients [8]. Other groups have proposed similar guidelines regarding triage and PPE for management of otolaryngology patients, and have reported changes in outpatient and operative otolaryngologic practice due to these guidelines [9][10][11][12]. However, to the best of our knowledge, no existing literature has characterized the impact of the pandemic on inpatient otolaryngologic consultations in the United States.…”
Section: Introductionmentioning
confidence: 99%